STRENGTHENING EMPLOYEE RETENTION THROUGH CAREER GROWTH: A SCOPUS-BASED BIBLIOMETRIC ANALYSIS - Ahmad, Noor Azinuddin; Cheng , Mui Li; Zulkepli, Masitah; Raman, Uma Devi; Maruthupillai, Vasanthan; Mazlam, Nor Fatihah; Mustapha, Nadwatul Husna; Yusoff, Nurza Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Rising employee mobility and mobility expectations, evolving employee needs and requirements, and increased competition to attract scarce talent have made career growth a priority in this study on employee retention. While previous studies have examined various factors that may affect retention, the literature remains fragmented. This deficit has been addressed by the study, which suggests an integrated review and systematic knowledge mapping in the period 2017-2026. The research was conducted through a literature review; data were retrieved from the Scopus Database, and 452 publications were qualified. In OpenRefine, the dataset was standardized and cleaned for accuracy. Bibliometric performance analysis and science mapping were conducted using Scopus Analyzer and VOSviewer software to provide information on publication trends, influential publications, countries, thematic clusters, and collaborations. The findings indicate that the volume of published work has continued to rise during this period, suggesting that the academic community has been growing in its interest in employee retention and the relationships between retention and career advancement. Keyword co-occurrence analysis has revealed dominant themes in the organizational context (commitment, career development), employee performance, and career adaptability/psychological capital. The most prominent research avenues are sustainable careers, protean career orientation and workplace well-being. There is also growing international cooperation reflected in the country co-authorship analysis of developed and developing countries. Moreover, the systematic and empirical mapping of the intellectual structure of employee retention research makes this research a broader contribution to the literature. It further identifies key strands of research and their modes of collaboration, and offers a synthesis that will inform the work of employees and those interested in creating retention plans based on long-term engagement with work and careers.